THEORETICAL STUDY OF INJECTOR TESTING USING ELECTRIC INJECTOR TESTING TOOLS - Agung Suprianto; Tuharno Tuharno (University of Merdeka Malang, 2019)
The development of technology, especially in the field of modern and sophisticated automotives, one of the technologies being developed is EFI (electronic fuel injection). EFI is a fuel spraying system whose performance is electrically controlled in order to obtain the value of the mixture of air and fuel that is in accordance with the needs of the combustion motor, so that optimal motor power can be obtained with minimal fuel use and has an environmentally friendly exhaust gas. The function and function of fuel injection system of the EFI system on the vehicle consists of three systems, especially the fuel system, the induction system and the electrical control system. The injector is an electromagnetic nozzle whose operation is controlled by the computer, the injector is equipped with a heat insulator on the inlet or on the cylinder line which is close to the input line. The way the injector works is as well as when the ECU sends its signal in the form of a solenoid coil then it must be converted into a magnet which will lift the nose to its upper position, so that the injector gate will open and the high pressure fuel supplied by the fuel pump can come out or spray gently. The electric injector is one of the only substances used to spray and atomize gasoline into the burner according to the Firing Order (FO) sequence.